Analysis of Shopee Application Transactions Using the ShopeePayLater Feature: Study of Takhrij and Syarah Hadith an Islamic Business Economic Approach - Nur Anisa; Widodo Dwi Ismail Aziz; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze the hadith about Shopee PayLater transactions in the Shopee application. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with sharia economic law analysis. The results of this study found that the quality status of the hadith was assessed as authentic based on the takhrij hadith so that the hadith of al-Bukhari no. 2086 can be used as evidence for Islamic practice. Syarah hadith shows that ShopeePayLater transactions are valid if they use a salam contract with an agreement between the consumer and the Shopee application. This study concludes that ShopeePayLater does seem to make it easier for consumers to transact but it needs to be balanced with understanding because it is feared that there will be consumptive and debt risks if used unwisely. This study recommends a review through a sharia economic law approach related to ShopeePayLater transactions in terms of buying and selling and their misuse in accordance with sharia provisions.